2020
DOI: 10.1136/jclinpath-2020-206581
|View full text |Cite
|
Sign up to set email alerts
|

Detection of microsatellite instability in a panel of solid tumours with the Idylla MSI Test using extracted DNA

Abstract: AimDuring the last few years, determination of microstatellite instability (MSI) status has become a routine part of clinical practice, essentially to detect Lynch syndrome. Recently, MSI testing has increased with the development of immunotherapy and has expanded to a large panel of solid tumours. The aim of our work was to evaluate a fully automated system developed by Biocartis, the Idylla MSI Test, which performs an MSI analysis within 150 min.MethodsA comparison between pentaplex PCR, immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…In colorectal cancers, sensitivity and specificity were 100% for samples with a tumor cell percentage above 30%. Our results are in agreement with other recent reports on the concordance in colorectal cancers between the Idylla MSI assay and IHC/PCR 26 , 41 44 . Also in endometrial cancer, all molecular methods in our study achieved comparable sensitivity—albeit lower than the sensitivity observed in colorectal cancers.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In colorectal cancers, sensitivity and specificity were 100% for samples with a tumor cell percentage above 30%. Our results are in agreement with other recent reports on the concordance in colorectal cancers between the Idylla MSI assay and IHC/PCR 26 , 41 44 . Also in endometrial cancer, all molecular methods in our study achieved comparable sensitivity—albeit lower than the sensitivity observed in colorectal cancers.…”
Section: Discussionsupporting
confidence: 94%
“…Hereby relevant tandem repeat loci are included in targeted NGS panels and indel length distributions of aligned reads are analysed. Another recent option is the fully automated Idylla MSI assay developed by Biocartis, which measures MSI using seven repeat markers within 150 min per sample including DNA extraction 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported about the performances of the Idylla MSI test (Biocartis) that allows fully‐automated and rapid (2.5 h) MSI testing and is usable even in pathology laboratories with no expertise in molecular pathology. These studies have particularly reported on the good performances of this test in CRC samples (about 98% sensitivity and 99% specificity about 2000 CRC samples tested in the literature) 9–13,15–20,22,23 . Series of non‐CRC tumors (about 1000 cases including several different organs and tumor types, as endometrial, urothelial, gastric, but also fewer duodenal–pancreatic, ovarian, prostatic, small‐intestine carcinomas, or cutaneous adnexal tumors) have also reported good performances of this Idylla MSI test with nervertheless inferior sensitivity in comparison with CRC (about 92% sensitivity and 99% specificity in non‐CRC tumors) 6–9,11,12,14,15,18,21,23,24 .…”
Section: Introductionmentioning
confidence: 93%
“…Over the years, propelled by technological advancements, the PCR‐MSI test has undergone continued modification, both with regard to marker amplification (simplex to multiplex PCR, radiolabelled primers to fluorescent primers) and fragment length detection post‐amplification (gel electrophoresis to capillary electrophoresis to other methods such as denaturing high‐performance liquid chromatography and high‐resolution melting analysis). The marker panels have also evolved, shifting to incorporate more mononucleotide markers due to the growing appreciation that such markers are quasi‐monomorphic (nearly all individuals have the same number of repeats at these alleles) and sensitive in detecting MMR deficiency 32 …”
Section: Msi Diversity Versus Effective Msi Testingmentioning
confidence: 99%